Polymer-crystalline structures of cutoff type with homogeneous layers of high refraction index - Belayeva, A.I.; Kolomiets, S.N. (Functional Materials, 2004)
Effect of design parameters on characteristics of cutoff and band polymer-crystalline systems with layers thickness divisible by λ/4 has been studied in detail. The polymer-germanium systems have been shown to be of the greatest practical interest. A method has been developed to smooth the secondary extremes in the transparence band of a quarterwave polymer-germanium cutoff filter by introduction of additional interference layers made of polyethylene. The possibility to form a band type spectral characteristic has been shown in experiment for polymer-germanium systems in far IR spectral region. Детально исследовано влияние конструктивных параметров на характеристики отрезающих и полосовых полимер-кристаллических систем со слоями кратными λ/4. Показано, что наибольший практический интерес представляют системы полимер-германий. Разработан метод сглаживания вторичных экстремумов в полосе прозрачности четвертьволнового отрезающего фильтра полимер-германий добавлением дополнительных интерференционных слоев из полиэтилена. Экспериментально показана возможность формирования спектральной характеристики полосового типа на системах полимер-германий в далекой ИК области спектра. Детально досліджєно вплив конструктивних napaмeтpiв на характеристики відрізаючих і смугових полімер-кристалічних систем із шарами кратними λ/4. Показано, що найбільший практичний інтерес представляють системи полімер-германій. Розроблено метод згладжування вторинних зкстремумів у смузі прозорості чвертьхвильового відрізаючого фільтра полімер-германій додаванням додаткових інтерференційних шарів з поліетилену. Експериментально показано можливість формування спектральної характеристики смугового типу на системах полімер-германій в далекій I4 області спектра.